To Individualisation of Subject (Donor) by Determination of Serological Markers from Obtain Biological Fluid at Crime Scene (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
For this study samples was collected from 20 donors with unknown blood group and secretor status had been determined from saliva by using biological fluid. ABO typing on the concentrated samples was successfully performed after 1 month of storage. Urine stained clothing samples are often submitted to forensic science laboratories for ABH blood group antigen determination. The serogenetic markers of semen stains submitted can be used to determine the origin of any of these samples. ABH blood group substances have previously been identified from urine. ABH blood group substance is low in urine in comparison with other body fluids.
Keywords: ABH blood group; body fluids; crime scene; serological markers; urine